Composite, catalyst ink, and method for producing composite

By developing a composite catalyst containing molybdenum disulfide and palladium, the shortcomings of catalyst materials in the prior art were solved, and efficient catalytic performance was achieved, which was suitable for hydrogen production catalysts and catalyst inks.

CN119421743APending Publication Date: 2025-02-11DIC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380044346.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-02
Filing Date
2023-08-02
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

There is a lack of novel catalyst materials in the prior art, especially in catalysts containing molybdenum disulfide, and their catalytic activity has not been fully utilized.

Method used

A composite was developed, including molybdenum disulfide particles and palladium particles, the average crystallite size of molybdenum disulfide particles is less than 150 nm, the average particle size of palladium particles is less than 20 nm, and palladium particles are present on the surface of molybdenum disulfide particles.

Benefits of technology

Through the use of this composite, efficient catalyst performance is achieved, suitable for hydrogen production catalysts such as water electrolysis, and can be used for catalyst inks forming catalyst layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119421743A_ABST
    Figure CN119421743A_ABST
Patent Text Reader

Abstract

Provided is a composite which contains molybdenum disulfide particles and palladium particles, and which is characterized in that the average crystallite size of molybdenum disulfide contained in the molybdenum disulfide particles is 150 nm or less, said average crystallite size being determined from a peak at 2 [theta] = 14.4 DEG +-0.5 DEG as determined by X-ray diffraction measurement. Also provided is a catalyst ink comprising the composite and a dispersion medium. Also provided is a method for producing the composite, which comprises a step for mixing a palladium solution with molybdenum disulfide particles, and which is characterized in that the average crystallite size of molybdenum disulfide contained in the molybdenum disulfide particles is 150 nm or less, said average crystallite size being determined from a peak at 2 [theta] = 14.4 DEG +-0.5 DEG as obtained by X-ray diffraction measurement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite material, a catalyst ink, and a method for manufacturing the composite material.

[0002] This application claims priority based on Japanese Patent Application No. 2022-123199 filed in Japan on August 2, 2022, the contents of which are incorporated herein by reference. Background Art

[0003] In the process of aiming to solve environmental and energy resource problems, water electrolysis technology has attracted much attention as a technology that can use electricity from renewable energy and produce hydrogen from water.

[0004] Layered transition metal chalcogenide compounds, represented by molybdenum disulfide (MoS2), are expected to be a material with low price, abundant resources and high catalytic activity.

[0005] Patent Document 1 discloses a method for producing molybdenum disulfide doped with metal ions. In addition, the metal cations of the metal doped are uniformly dispersed between the layers of molybdenum disulfide, and it is believed that the material maintains the two-dimensional sheet structure of molybdenum disulfide in the crystal structure.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Chinese Patent Application Publication No. 106608652 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, there is still room for research on providing novel catalyst materials comprising molybdenum disulfide.

[0011] An object of the present invention is to provide a composite material that can be used as a catalyst, a catalyst ink, and a method for producing the composite material.

[0012] Means for solving problems

[0013] The present invention has the following aspects.

[0014] <1> A composite comprising molybdenum disulfide particles and palladium particles, wherein the average crystallite size of molybdenum disulfide contained in the molybdenum disulfide particles is 150 nm or less, the average crystallite size being determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement.

[0015] <2> The composite according to <1> above, wherein the average particle size of the palladium particles is 20 nm or less.

[0016] <3> The composite according to <1> or <2>, wherein the palladium particles are present on the surface of the molybdenum disulfide particles.

[0017] <4> The composite according to any one of <1> to <3>, wherein the palladium particles include an aggregate of palladium atoms having no crystal structure.

[0018] <5> The composite according to any one of <1> to <4>, wherein the median particle size D of the composite determined by a dynamic light scattering method is 50 Below 1000nm.

[0019] <6> The composite according to any one of <1> to <5>, wherein the specific surface area of ​​the composite measured by the BET method is 10 m 2 / g and above and 200m 2 / g or less.

[0020] <7> The composite material according to any one of <1> to <6>, wherein the content of palladium determined by XRF analysis is 0.1% by mass or more relative to the total mass of the composite material.

[0021] <8> The composite according to any one of <1> to <7>, wherein the molybdenum disulfide contained in the molybdenum disulfide particles has a 3R crystal structure.

[0022] <9> The composite material according to any one of <1> to <8>, wherein the primary particles of the molybdenum disulfide particles are in the form of ropes, ribbons or sheets, and have an average thickness of 50 nm or less.

[0023] <10> A catalyst ink comprising the composite according to any one of <1> to <9> and a solvent.

[0024] <11> A method for producing a composite as described in any one of <1> to <9>, comprising the step of mixing molybdenum disulfide particles with a palladium solution, wherein the average crystallite size of molybdenum disulfide contained in the molybdenum disulfide particles is less than 150 nm, and the average crystallite size is determined based on the peak of 2θ=14.4°±0.5° obtained by X-ray diffraction measurement.

[0025] Effects of the Invention

[0026] According to the present invention, a composite material that can be used as a catalyst, a catalyst ink, and a method for producing the composite material can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] [ Figure 1] is a schematic diagram showing an example of an apparatus for producing molybdenum trioxide particles, which are the raw material of molybdenum disulfide particles of the composite of the embodiment.

[0028] [ Figure 2 ] is a graph showing the superposition of X-ray diffraction (XRD) curves of the particles obtained in Synthesis Example 1, Examples 1 to 4, and Comparative Example 1.

[0029] [ Figure 3 ] is a transmission electron microscope (TEM) image of each particle obtained in Synthesis Example 1, Examples 1 to 4, and Comparative Example 1.

[0030] [ Figure 4 ] is an image showing a high-resolution transmission electron microscope (HR-TEM) image of the composite particles obtained in Example 2, and an image of the elemental mapping results obtained using energy dispersive X-ray spectroscopy (EDS).

[0031] [ Figure 5 ] are the HAADF-STEM image (transmission electron image) and SEI image (secondary electron image) of the composite particles obtained in Example 2. DETAILED DESCRIPTION

[0032] Hereinafter, embodiments of the composite, catalyst ink, and method for producing the composite according to the present invention will be described.

[0033] <<Compound>>

[0034] The composite of the embodiment includes molybdenum disulfide particles and palladium particles. The average crystallite size of molybdenum disulfide contained in the molybdenum disulfide particles is 150 nm or less, and the average crystallite size is obtained from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement.

[0035] The composite of the embodiment has a structure in which the above-mentioned molybdenum disulfide particles and the above-mentioned palladium particles are composited.

[0036] In this specification, the above-mentioned "complex" may be a state in which the molybdenum disulfide particles and the palladium particles are integrated through any interaction. The above-mentioned interaction is not particularly limited, and it can be assumed to be a physical interaction between the surface of the molybdenum disulfide particle (for example, if the shape of the molybdenum disulfide particle is a sheet or a band (described below), it is assumed to be a concave or wrinkled part of the surface) and the surface of the palladium particle, or a chemical bond such as a coordination bond, an ionic bond, an intermolecular force, such as a bond between S-Pd.

[0037] The average crystallite size of molybdenum disulfide contained in the molybdenum disulfide particles, determined from the peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement, is 150 nm or less, preferably 50 nm or less, more preferably 40 nm or less, further preferably 20 nm or less, particularly preferably 10 nm or less, and particularly preferably less than 6 nm.

[0038] The peak of 2θ=14.4°±0.5° belongs to the (002) plane or (003) plane of molybdenum disulfide (MoS2). If the average crystallite size is a smaller value as below the above upper limit, the catalyst active sites such as interfaces and defects that contribute to the catalyst activity increase, and the catalyst performance is improved.

[0039] The lower limit of the average crystallite size of the molybdenum disulfide determined from the peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement may be, for example, 1 nm or more, 2 nm or more, or 3 nm or more.

[0040] As an example of the numerical range of the above-mentioned numerical value of the average crystallite size calculated based on the peak of 2θ=14.4°±0.5° obtained by X-ray diffraction measurement of the above-mentioned molybdenum disulfide, it can be greater than 1 nm and less than 150 nm, greater than 2 nm and less than 50 nm, greater than 2 nm and less than 40 nm, greater than 3 nm and less than 20 nm, greater than 3 nm and less than 10 nm, or greater than 3 nm and less than 6 nm.

[0041] The above-mentioned average crystallite size of molybdenum disulfide contained in the molybdenum disulfide particles of the embodiment can be specified by the following measurement method.

[0042] [Determination of crystallite size]

[0043] An X-ray diffraction apparatus (e.g., SmartLab 9kV manufactured by Rigaku Co., Ltd.) is used, a scintillation counter is used as a detector, and analysis software (e.g., PDXL2) is used for measurement. The measurement method is the 2θ / θ method, and the Scherrer formula is used to calculate the average crystallite size based on the half-height width of the peak appearing in the range of 2θ=14.4°±0.5°. As measurement conditions, the scanning speed (2θ) is 2.0° / min, the scanning range (2θ) is 10-70°, the spacing (2θ) is 0.02°, and the device standard width is set to none.

[0044] The composite material of the embodiment may be a granular structure (composite particles).

[0045] The median particle size D of the composite according to the embodiment determined by the dynamic light scattering method is 50It is preferably 1000 nm or less, more preferably 600 nm or less, and still more preferably 500 nm or less.

[0046] The median particle size D 50 A composite having an upper limit value or less can more effectively exhibit catalytic efficiency.

[0047] Median particle size D of the composite according to the embodiment determined by dynamic light scattering 50 As an example, it may be greater than 20 nm, greater than 40 nm, greater than 100 nm, or greater than 300 nm.

[0048] The median particle size D of the composite obtained by the dynamic light scattering method as an embodiment 50 An example of the numerical range of the above numerical value may be greater than or equal to 20 nm and less than or equal to 1000 nm, may be greater than or equal to 40 nm and less than or equal to 600 nm, may be greater than or equal to 100 nm and less than or equal to 500 nm, or may be greater than or equal to 300 nm and less than or equal to 500 nm.

[0049] The median particle size D calculated by the dynamic light scattering method of the composite according to the embodiment 50 , can be obtained in the following manner: using a dynamic light scattering particle size distribution measuring apparatus (e.g. Nanotrac Wave II manufactured by Microtrac BEL), using acetone as a medium to measure the particle size distribution by a wet method, in which the particle size distribution is obtained when the volume cumulative % ratio becomes 50%.

[0050] The specific surface area of ​​the composite of the embodiment measured by the BET method is preferably 10 m 2 / g or more, more preferably 30m 2 / g or more, more preferably 40m 2 / g or above.

[0051] The composite having a specific surface area equal to or greater than the lower limit has a larger specific surface area, and thus has more catalyst active sites and facilitates the movement of substances in the reaction system, thereby more effectively improving the catalyst efficiency.

[0052] The specific surface area of ​​the composite of the embodiment measured by the BET method may be, for example, 200 m 2 / g or less, also 100m 2 / g or less.

[0053] An example of the numerical range of the above-mentioned numerical value of the specific surface area measured by the BET method of the composite of the embodiment is 10 m 2 / g and above and 200m 2 / g or less, also 30m 2 / g and above and 200m 2 / g or less, also 40m 2 / g or more and 100m 2 / g or less.

[0054] The specific surface area is measured using a specific surface area meter (e.g., BELSORP-mini manufactured by Microtrac BEL), and the surface area per 1 g of the sample measured using the BET method (Brunauer-Emmett-Teller method) is calculated based on the amount of nitrogen adsorption and is taken as the specific surface area (m 2 / g).

[0055] The palladium content of the composite of the embodiment determined by X-ray fluorescence (XRF) analysis is preferably 0.1 mass % or more, more preferably 0.5 mass % or more, and even more preferably 1 mass % or more, relative to the total mass (100 mass %) of the composite.

[0056] A composite having a palladium content ratio of not less than the above lower limit can more effectively exhibit the catalytic efficiency derived from palladium.

[0057] The palladium content of the composite of the embodiment determined by XRF analysis may be, for example, 20 mass % or less, 15 mass % or less, or 12 mass % or less relative to the total mass (100 mass %) of the composite.

[0058] As an example of the numerical range of the above-mentioned numerical value of the ratio of the palladium content of the composite as determined by XRF analysis to the total mass (100 mass %) of the above-mentioned composite, it may be greater than 0.1 mass % and less than 20 mass %, greater than 0.5 mass % and less than 15 mass %, or greater than 1 mass % and less than 12 mass %.

[0059] The molybdenum content of the composite of the embodiment determined by X-ray fluorescence (XRF) analysis may be 30 mass % or more, 40 mass % or more, or 50 mass % or more relative to the total mass (100 mass %) of the composite.

[0060] The molybdenum content of the composite of the embodiment determined by XRF analysis may be, for example, 80 mass % or less, 75 mass % or less, or 70 mass % or less relative to the total mass (100 mass %) of the composite.

[0061] As an example of the numerical range of the above-mentioned numerical value of the ratio of the molybdenum content of the composite determined by XRF analysis as an embodiment to the total mass (100 mass %) of the above-mentioned composite, it may be greater than 30 mass % and less than 80 mass %, greater than 40 mass % and less than 75 mass %, or greater than 50 mass % and less than 70 mass %.

[0062] The sulfur content of the composite of the embodiment determined by X-ray fluorescence (XRF) analysis may be 15 mass % or more, 20 mass % or more, or 25 mass % or more relative to the total mass (100 mass %) of the composite.

[0063] The ratio of the sulfur content of the composite of the embodiment determined by XRF analysis to the total mass (100 mass%) of the composite may be, for example, 50 mass% or less, 45 mass% or less, or 40 mass% or less.

[0064] As an example of the numerical range of the above-mentioned numerical value of the ratio of the sulfur content of the composite as determined by XRF analysis of the embodiment to the total mass (100 mass %) of the above-mentioned composite, it may be greater than 15 mass % and less than 50 mass %, greater than 20 mass % and less than 45 mass %, or greater than 25 mass % and less than 40 mass %.

[0065] Hereinafter, the molybdenum disulfide particles and the palladium particles will be described in detail.

[0066] <Molybdenum disulfide particles>

[0067] The molybdenum disulfide particles contained in the composite of the embodiment are composited with the above-mentioned palladium particles to form a composite.

[0068] The shape of the primary particles of the molybdenum disulfide particles in the composite of the embodiment in the two-dimensional image obtained by photographing the molybdenum disulfide particles using a transmission electron microscope (TEM) can be any shape, preferably granular, spherical, plate-like, needle-like, rope-like, ribbon-like or sheet-like, more preferably rope-like, ribbon-like or sheet-like. The molybdenum disulfide particles may also include a combination of these shapes.

[0069] Here, being in a strip shape or a sheet shape means being in a thin layer shape, and being in a strip shape means being in a long thin layer shape.

[0070] When the shape of the primary particles of the molybdenum disulfide particle portion is rope-shaped, belt-shaped or sheet-shaped, the average value of the thickness obtained by measuring 50 primary particles of the molybdenum disulfide particle portion is preferably less than 100 nm, more preferably less than 50 nm, further preferably less than 30 nm, and particularly preferably less than 15 nm.

[0071] As an example of the numerical range of the above-mentioned thickness, when the shape of the primary particles of the molybdenum disulfide particle portion is rope-shaped, belt-shaped or sheet-shaped, the average value of the thickness obtained by measuring 50 primary particles of the molybdenum disulfide particle portion can be 1 to 100 nm, 3 to 50 nm, 5 to 30 nm, or 5 to 15 nm.

[0072] The shape of the molybdenum disulfide particle part is preferably a rope, a belt or a sheet. The shape of 50 primary particles of the molybdenum disulfide particle part is preferably a size in the range of length (vertical) × width (horizontal) × thickness (height) = 50 to 1000 nm × 50 to 1000 nm × 3 to 100 nm, more preferably a size in the range of 100 to 500 nm × 100 to 500 nm × 5 to 50 nm, and particularly preferably a size in the range of 50 to 200 nm × 50 to 200 nm × 5 to 20 nm. By being in the shape of a rope, a belt or a sheet, the specific surface area of ​​the molybdenum disulfide particle part can be increased. The aspect ratio of the primary particles of the molybdenum disulfide particle part, that is, the value of (length (vertical and horizontal size)) / thickness (height)) is preferably 1.2 to 1200, more preferably 2 to 800, further preferably 5 to 400, and particularly preferably 10 to 200.

[0073] The length, width, and thickness of the molybdenum disulfide particle portion can be measured using an atomic force microscope (AFM).

[0074] The shape of the primary particles of the molybdenum disulfide particles is not simply spherical, but is in the shape of ropes, ribbons or sheets with a large aspect ratio, so that the specific surface area is increased, and the catalyst efficiency can be effectively improved.

[0075] The molybdenum disulfide particles contain molybdenum disulfide (MoS2). The composite of the embodiment preferably contains 50 mass% or more of molybdenum disulfide (MoS2) relative to the total mass (100 mass%) of the composite, more preferably 80 mass% or more, and even more preferably 85 mass% or more.

[0076] The composite having the molybdenum disulfide content ratio being equal to or greater than the lower limit can more effectively exhibit the catalytic efficiency derived from the molybdenum disulfide.

[0077] As the upper limit of the content of molybdenum disulfide (MoS2) relative to the total mass (100 mass%) of the composite, the content value can be set so that the sum of the contents of molybdenum disulfide (MoS2), palladium (Pd), and any components that may be contained in the composite of the embodiment does not exceed the total mass (100 mass%) of the composite. As an example, it can be less than 99.9 mass%, less than 99.5 mass%, or less than 99.0 mass%.

[0078] Furthermore, the content of the above-mentioned molybdenum disulfide (MoS2) can be a value obtained by XRF analysis, and can be calculated as the sum of the molybdenum content and the sulfur content of the composite of the above-mentioned embodiment obtained by XRF analysis.

[0079] As one embodiment, the following composite material can be exemplified: a composite material in which, as determined by XRF analysis, the proportion of palladium content is greater than 0.1 mass % and less than 20 mass %, and the proportion of molybdenum disulfide (MoS2) content is greater than 80 mass % and less than 99.9 mass %; a composite material in which, as determined by XRF analysis, the proportion of palladium content is greater than 0.5 mass % and less than 15 mass %, and the proportion of molybdenum disulfide (MoS2) content is greater than 85 mass % and less than 99.5 mass %; a composite material in which, as determined by XRF analysis, the proportion of palladium content is greater than 1 mass % and less than 12 mass %, and the proportion of molybdenum disulfide (MoS2) content is greater than 88 mass % and less than 99 mass %

[0080] Furthermore, the composite of the embodiment can be provided in the form of an aggregate of composite particles (e.g., powder). If the aggregate contains molybdenum disulfide (MoS2), it can contain a x Molybdenum sulfide particles of one or more molybdenum sulfide represented by (X=1 to 3).

[0081] In addition, the above average crystallite size, D 50 , specific surface area, and values ​​related to XRF analysis can be obtained by measuring an aggregate of composite particles (such as powder) as a sample.

[0082] The conversion rate R of the above molybdenum disulfide particles to MoS2 C It is preferably 70% or more, more preferably 80% or more, and still more preferably 90% or more.

[0083] The conversion rate R to MoS2 C When the content is not less than the above lower limit, the catalyst performance can be more effectively exhibited.

[0084] Conversion rate R of MoS2 particles to MoS2 C It can be obtained by using the RIR (reference intensity ratio) method based on the graph data obtained by X-ray diffraction (XRD) measurement of molybdenum disulfide particles. The RIR value K of molybdenum disulfide (MoS2) can be used. A, and the integrated intensity I of the peak near 2θ=14.4°±0.5° at the (002) plane or (003) plane of molybdenum disulfide (MoS2) A , and each molybdenum oxide (MoO3 as a raw material and Mo9O as a reaction intermediate) 25 、Mo4O 11 , MoO2, etc.) B and each molybdenum oxide (MoO3 as a raw material and Mo9O as a reaction intermediate) 25 、Mo4O 11 The integrated intensity I of the strongest line peak of B The conversion rate R to MoS2 is calculated according to the following formula (1): C .

[0085] R C (%)=(I A / K A ) / (Σ(I B / K B ))×100··· (1)

[0086] Here, the RIR values ​​may be values ​​recorded in the Inorganic Crystal Structure Database (ICSD) (created by the Japan Association for International Chemical Information), and comprehensive powder X-ray analysis software (manufactured by Rigaku Corporation, PDXL2) may be used for analysis.

[0087] As another embodiment, the molybdenum disulfide contained in the molybdenum disulfide particles may include a 3R crystal structure, or may include a 2H crystal structure and a 3R crystal structure.

[0088] Such molybdenum disulfide particles containing 2H crystal structure and 3R crystal structure are products independently developed by the applicant, and as their crystal structure, they have not only 2H structure but also rare 3R (rhombohedral) structure. The 3R structure tends to have a skewed crystal structure and has more catalyst active sites, so the inclusion of 3R crystal structure in molybdenum disulfide helps to improve catalyst performance.

[0089] The molybdenum disulfide particles containing a 3R crystal structure can be produced, for example, by the <Method for producing molybdenum disulfide particles> described later, and the following molybdenum disulfide can be synthesized, which contains a 3R structure that is difficult to achieve by crushing minerals or synthesizing from general molybdenum trioxide, and is advantageous for nm scale and large surface area.

[0090] The abundance ratio of the 3R crystal structure in the crystal phase of molybdenum disulfide may be 5% to 60%, 10% to 60%, 20% to 60%, or 20% to 45%.

[0091] The molybdenum disulfide particles have a 2H crystal structure and a 3R crystal structure, for example, can be confirmed using an expanded Rietveld analysis software (manufactured by Malvern Panalytical, HighScorePlus) that can take into account the crystallite size. The Rietveld analysis software uses a crystal structure model including the crystallite size to simulate the entire diffraction pattern of XRD, and compares it with the diffraction pattern of XRD obtained by experiment. In a manner that the residual between the diffraction pattern obtained by experiment and the diffraction pattern obtained by calculation is minimized, the crystal structure factors such as the lattice constant and atomic coordinates of the crystal structure model, and the weight fraction (abundance ratio) are optimized using the least squares method, and each phase of the 2H crystal structure and the 3R crystal structure is identified and quantified with high precision. Thus, in addition to calculating the crystal structure type and its ratio calculated by the usual Rietveld analysis, the crystallite size can also be calculated. Hereinafter, in this specification, the above-mentioned analysis method using HighScore Plus is referred to as "expanded Rietveld analysis".

[0092] In addition, in the molybdenum disulfide particles, the crystallite size of the above-mentioned 3R crystal structure obtained using the pattern obtained according to the above-mentioned XRD and by the expanded Rietveld analysis can be greater than 1 nm and less than 150 nm, and is preferably composed of a crystalline phase composed of crystallites of greater than 5 nm and less than 50 nm, and the above-mentioned crystallite size is more preferably greater than 10 nm and less than 40 nm.

[0093] In addition, in the molybdenum disulfide particles of the present embodiment, the crystallite size of the above-mentioned 2H crystal structure obtained using the pattern obtained according to the above-mentioned XRD and by the expanded Rietveld analysis is preferably greater than 1 nm and less than 150 nm, and is preferably a crystalline phase composed of crystallites greater than 1 nm and less than 150 nm, and the above-mentioned crystallite size is more preferably greater than 5 nm and less than 150 nm.

[0094] The 2H crystal structure obtained by the extended Rietveld analysis is preferably composed of a crystalline phase composed of crystallites having a predetermined crystallite size. In this case, the crystallite size of the 2H crystal structure is more preferably 1 nm to 20 nm, preferably 5 nm to 15 nm.

[0095] The crystallite size of the 2H crystal structure and the crystallite size of the 3R crystal structure can also be calculated using, for example, the peak half-width of an XRD diffraction pattern.

[0096] The abundance ratio (2H:3R) of the 2H crystal structure and the 3R crystal structure in the crystal phase obtained by the extended Rietveld analysis using the pattern obtained by the XRD is preferably 10:90 to 90:10.

[0097] From the perspective of the above-mentioned effects, the abundance ratio (2H:3R) of the above-mentioned 2H crystal structure and the above-mentioned 3R crystal structure in the crystal phase obtained using the pattern obtained according to the above-mentioned XRD and by expanded Rietveld analysis is more preferably 10:90 to 80:20, and further preferably 40:60 to 80:20.

[0098] In addition, the 2H crystal structure obtained by the expanded Rietveld analysis may be composed of the following crystal phases: a first crystal phase composed of crystallites having a predetermined crystallite size, and a second crystal phase having a crystallite size smaller than the first crystal phase. The crystallite size of the first crystal phase of the 2H crystal structure is, for example, greater than 20 nm and less than 150 nm, or greater than 50 nm and less than 150 nm, or greater than 100 nm and less than 150 nm. Among them, it is preferred that the first crystal phase does not exist in the crystal phase of the 2H crystal structure, or its abundance is relatively small. In addition, the crystallite size of the second crystal phase of the 2H crystal structure is preferably greater than 1 nm and less than 20 nm, or greater than 1 nm and less than 10 nm, or greater than 5 nm and less than 15 nm.

[0099] The crystallite size of the first crystalline phase of the 2H crystal structure, the crystallite size of the 3R crystal structure, and the crystallite size of the second crystalline phase of the 2H crystal structure can be calculated in the same manner as described above, for example, using the peak half-width of the XRD diffraction pattern.

[0100] The abundance ratio of the above-mentioned first crystalline phase of the above-mentioned 2H crystal structure, the above-mentioned 3R crystal structure, and the above-mentioned second crystalline phase of the above-mentioned 2H crystal structure in the crystalline phase obtained using the pattern obtained according to the above-mentioned XRD and through the expanded Rietveld analysis (2H (first crystalline phase): 3R: 2H (second crystalline phase)) is preferably 30~0:10~70:80~15, and more preferably 25~0:20~60:75~20.

[0101] In the pattern obtained by powder X-ray diffraction (XRD) of the molybdenum disulfide particles using Cu-Kα rays as an X-ray source, it is preferred that the peak near 2θ=39.5° and the peak near 49.5° are derived from the 2H crystal structure, the peak near 2θ=32.5°, the peak near 39.5°, and the peak near 49.5° are derived from the 3R crystal structure, and the half-width of the peak near 2θ=39.5° and the peak near 49.5° is 1° or more. Furthermore, the molybdenum disulfide particles may include a crystal structure other than the 2H crystal structure and the 3R crystal structure of molybdenum disulfide, such as a 1H crystal structure.

[0102] The fact that the above-mentioned molybdenum disulfide particles contain a 3R crystal structure with a metastable structure can be distinguished in the following manner: in the pattern obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source, the peak near 2θ=39.5° and the peak near 2θ=49.5° are both composed of synthetic peaks of the 2H crystal structure and the 3R crystal structure.

[0103] In fact, using the pattern obtained by the above-mentioned powder X-ray diffraction (XRD), the abundance ratio of the 2H crystal structure is determined from the peak near 2θ=39.5° and the broad peak near 49.5°. In addition, the difference between the peak near 2θ=39.5° and the broad peak near 49.5° is optimized using the two peaks near 2θ=32.5° and the two peaks near 39.5°, thereby determining the abundance ratio of the 3R crystal structure. That is, the peak near 2θ=39.5° and the peak near 49.5° are both synthetic waves from the 2H crystal structure and the 3R crystal structure, and the abundance ratio of the 2H crystal structure and the 3R crystal structure in the molybdenum disulfide particles can be calculated from these synthetic waves.

[0104] The molybdenum disulfide particles may also contain an amorphous phase. The abundance ratio of the amorphous phase of the molybdenum disulfide particles is represented by 100 (%) - (crystallinity (%)), and is preferably 5% or more, more preferably 15% or more, and even more preferably 20% or more.

[0105] In the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) graph of the above-mentioned molybdenum disulfide particles based on the K absorption edge of molybdenum, the ratio of the peak intensity I caused by Mo-S to the peak intensity II caused by Mo-Mo (I / II) is preferably greater than 1.0, more preferably greater than 1.1, and particularly preferably greater than 1.2.

[0106] Regardless of whether the crystal structure of molybdenum disulfide is a 2H crystal structure or a 3R crystal structure, the distance between Mo-S is almost the same due to the covalent bond, so the intensity of the peak caused by Mo-S in the extended X-ray absorption fine structure (EXAFS) graph of the K absorption edge of molybdenum is the same.

[0107] On the other hand, since the 2H crystal structure of molybdenum disulfide is hexagonal, the same hexagon exists right below the 90° hexagon of the Mo atom, so the distance between Mo-Mo becomes closer and the peak intensity II caused by Mo-Mo becomes stronger.

[0108] On the contrary, since the 3R crystal structure of molybdenum disulfide is rhombohedral, the hexagon does not exist directly below 90° of the hexagon but exists halfway, so the distance between Mo-Mo becomes longer and the peak intensity II caused by Mo-Mo becomes weaker.

[0109] In a pure 2H crystal structure of molybdenum disulfide, the above ratio (I / II) becomes smaller, but as a 3R crystal structure is included, the above ratio (I / II) becomes larger.

[0110] <Palladium particles>

[0111] The palladium particles contained in the composite of the embodiment are a granular structure containing palladium, and are composited with the above-mentioned molybdenum disulfide particles to form a composite.

[0112] The shape of the palladium particles is not particularly limited, and examples thereof include a spherical shape, a hemispherical shape, a linear shape connecting a plurality of palladium particles, and a shape formed by combining these shapes.

[0113] The form of the palladium particles contained in the composite of the embodiment is not particularly limited. The palladium particles may be present on the surface of the molybdenum disulfide particles, or may be attached to or bonded to the surface of the molybdenum disulfide particles.

[0114] The number of palladium particles present per 100 nm×100 nm of the surface area of ​​the molybdenum disulfide particles confirmed in a two-dimensional image obtained by photographing the composite using a transmission electron microscope (TEM) may be, for example, 5 to 5000, or 10 to 1000.

[0115] The average particle size of the palladium particles may be 20 nm or less, 15 nm or less, or 13 nm or less.

[0116] As a lower limit of the average particle size of the palladium particles, for example, it may be 0.5 nm or more, 0.7 nm or more, or 1 nm or more.

[0117] An example of the numerical range of the numerical value of the average particle size of the palladium particles may be 0.5 nm to 20 nm, 0.7 nm to 15 nm, or 1 nm to 13 nm.

[0118] The average particle size of the palladium particles is an average value obtained by measuring the maximum length of the distance between two points on the contour line of 50 randomly selected palladium particles (wherein, palladium particles in a state where multiple palladium particles are aggregated are not selected) for palladium particles photographed by a transmission electron microscope (TEM) and confirmed on a two-dimensional image, and the average value of the maximum length is used.

[0119] The palladium particles contain palladium. The palladium contained in the composite of the embodiment is not particularly limited in the form in which it is contained, and for example, the palladium may be contained in the palladium particles as a palladium compound.

[0120] Among them, as shown in the examples described later, the following results were obtained: the XRD pattern of the spectrum obtained by XRD analysis did not show the crystal structure of palladium metal crystals; at least a portion of the palladium constituted palladium particles, and the palladium particles were observed to be attached or bonded to the surface of molybdenum disulfide particles; no changes were found in the layer spacing constituting molybdenum disulfide; and the valence of palladium was 0, etc.

[0121] Based on these contents, the palladium particles may include palladium without a crystal structure. The palladium particles may include palladium without a crystal structure of palladium metal crystals. The palladium particles may include palladium in a form other than a part of the molybdenum that replaces the crystal structure of molybdenum disulfide. The palladium particles may include zero-valent palladium.

[0122] Regarding the proportion of palladium in the above-mentioned contained form, the above-mentioned palladium particles may contain 50% or more of palladium without a crystalline structure on a molar basis relative to the palladium contained in the palladium particles. The above-mentioned palladium particles may contain 50% or more of palladium without a crystalline structure of palladium metal crystals on a molar basis relative to the palladium contained in the palladium particles. The above-mentioned palladium particles may contain 50% or more of palladium in a form that is not a part of the molybdenum having a crystalline structure that replaces molybdenum disulfide on a molar basis relative to the palladium contained in the palladium particles. The above-mentioned palladium particles may contain 50% or more of zero-valent palladium on a molar basis relative to the palladium contained in the palladium particles.

[0123] The palladium particles may include an aggregate of palladium atoms, and may include an aggregate of palladium atoms that do not have a crystal structure. The palladium particles may include an aggregate of palladium atoms that do not have a crystal structure of palladium metal crystals. The palladium particles may include an aggregate of palladium atoms that are not in the form of a portion of molybdenum that replaces the crystal structure of molybdenum disulfide. The palladium particles may include an aggregate of zero-valent palladium atoms.

[0124] The palladium contained in the palladium particles preferably does not have a crystal structure, and more preferably does not have a crystal structure of a palladium metal crystal.

[0125] Likewise, the composite of the embodiment may include palladium that does not have a crystal structure. The composite of the embodiment may include palladium that does not have a crystal structure of palladium metal crystals. The composite of the embodiment may include palladium in a form other than a portion of molybdenum that replaces the crystal structure of molybdenum disulfide. The composite of the embodiment may include palladium having a valence of 0.

[0126] Regarding the proportion of palladium in the above-mentioned contained forms, the composite of the embodiment may contain 50% or more of palladium without a crystalline structure, calculated on a molar basis, relative to the palladium contained in the composite. The composite of the embodiment may contain 50% or more of palladium without a crystalline structure, calculated on a molar basis, relative to the palladium contained in the composite. The composite of the embodiment may contain 50% or more of palladium in a form that is not a part of molybdenum having a crystalline structure that replaces molybdenum disulfide, calculated on a molar basis, relative to the palladium contained in the composite. The composite of the embodiment may contain 50% or more of palladium with a valence of 0, calculated on a molar basis, relative to the palladium contained in the composite.

[0127] Likewise, the composite of the embodiment may include a collection of palladium atoms that do not have a crystal structure. The composite of the embodiment may include a collection of palladium atoms that do not have a crystal structure of palladium metal crystals. The composite of the embodiment may include a collection of palladium atoms that are not in a form of molybdenum that replaces a portion of the crystal structure of molybdenum disulfide. The composite of the embodiment may include a collection of palladium atoms with a valence of 0.

[0128] The palladium contained in the composite of the embodiment preferably does not have a crystal structure, and more preferably does not have a crystal structure of palladium metal crystals.

[0129] As another embodiment, the composite of the embodiment may include a composite comprising molybdenum disulfide particles and palladium particles, wherein the average crystallite size of the molybdenum disulfide contained in the molybdenum disulfide particles, as determined from the peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement, is less than 150 nm (excluding composites in which the palladium contained in the composite has a crystal structure of palladium metal crystals).

[0130] The palladium in the composite of the embodiment may form a palladium cluster. Alternatively, the palladium in the palladium particles may form a palladium cluster.

[0131] The presence of a crystal structure containing palladium can be detected based on a diffraction pattern obtained by X-ray diffraction analysis using the composite of the embodiment as a sample, or can be detected based on analysis of the crystal structure by electron diffraction.

[0132] According to the composite of the embodiment described above, excellent catalytic performance can be exhibited by forming a composite of molybdenum disulfide particles having a minute crystallite size such as the average crystallite size of 150 nm or less and palladium particles.

[0133] Furthermore, it is considered that the palladium in the palladium particles does not constitute a crystal structure of palladium metal crystals, but is preferably present in the molybdenum disulfide particles in the form of an aggregate of palladium (Pd) atoms, and thus can exhibit more excellent catalyst performance.

[0134] The composite of the embodiment can be used as a catalyst, and in particular, can be suitably used as a hydrogen production catalyst applied to water electrolysis and the like.

[0135] Furthermore, the composite material of the embodiment can be suitably used as a constituent material of a catalyst ink that can form a catalyst layer.

[0136] Furthermore, the composite material of the embodiment can be suitably used as an electrode material used as a constituent material of an electrode catalyst layer.

[0137] <<Method for producing composite material>>

[0138] The method for manufacturing the composite of the embodiment includes the step of mixing molybdenum disulfide particles with a palladium solution, and the average crystallite size of molybdenum disulfide contained in the above-mentioned molybdenum disulfide particles is less than 150nm, and the average crystallite size is obtained based on the peak of 2θ=14.4°±0.5° obtained by X-ray diffraction measurement.

[0139] According to the method for producing a composite material of the embodiment, the composite material of the above-described embodiment can be produced.

[0140] Examples of the molybdenum disulfide particles include the molybdenum disulfide particles exemplified in the above-mentioned <<Composite>>.

[0141] The palladium solution can be obtained by dissolving any palladium source in a solvent.

[0142] The palladium source may be any source as long as a palladium solution can be produced, and examples thereof include palladium compounds such as palladium acetate, palladium nitrate, palladium nitrite, palladium sulfate, palladium carbonate, palladium chloride, palladium hydroxide, and palladium oxide.

[0143] The solvent may be any solvent as long as it can dissolve the palladium source, and examples thereof include alcohols such as methanol, benzene, dichloromethane, acetone, and chloroform.

[0144] The mixing method is not particularly limited, but preferably the palladium solution is mixed with the dispersion of molybdenum disulfide particles.

[0145] The dispersion of molybdenum disulfide particles can be obtained by mixing the solvent exemplified in the above palladium solution with the molybdenum disulfide particles.

[0146] A complex of the molybdenum disulfide particles and the palladium particles can be formed by mixing a palladium solution and molybdenum disulfide particles to obtain a mixture and bringing the molybdenum disulfide particles into contact with the palladium solution.

[0147] From the viewpoint of preventing aggregation of molybdenum disulfide particles, for example, it is preferable to stir the mixture of the palladium solution and the molybdenum disulfide particles. The stirring speed can be, for example, 50 to 1000 rpm.

[0148] The concentration of palladium in the palladium solution may be, for example, 0.00001 to 0.1 mol / L, or 0.0001 to 0.01 mol / L.

[0149] The temperature of the mixture of the molybdenum disulfide particles and the palladium solution may be such that a complex can be formed, and as an example, it may be 10 to 100°C, or 20 to 80°C.

[0150] The retention time of the mixture of molybdenum disulfide particles and palladium solution may be any time sufficient to form a complex, and as an example, may be 10 minutes to 48 hours, or 30 minutes to 12 hours.

[0151] In the method for producing the composite of the embodiment, in order to promote the photoreduction of palladium, the mixture of the molybdenum disulfide particles and the palladium solution can be irradiated with light. Regarding the light irradiation, the light amount and wavelength can be appropriately selected in a manner to achieve the degree of photoreduction of palladium. The light irradiation can be implemented by setting a light source to control the degree of light, or it can be irradiation with light in a general indoor environment (based on lighting such as fluorescent lamps, LEDs, etc.), irradiation with natural light, etc.

[0152] In the method for producing molybdenum disulfide described later, the production process includes a heating operation. However, in the method for producing the composite of the embodiment, the composite can be produced even without performing a heat treatment. For example, the obtained composite or the mixture of the palladium solution and the molybdenum disulfide particles is preferably not heated at 200° C. or more, more preferably not heated at more than 100° C., and even more preferably not heated at more than 80° C.

[0153] After the composite is formed from the mixture, the composite can be separated by centrifugal separation, drying, or the like, and the composite of the embodiment can be easily recovered.

[0154] The method for producing the composite according to the embodiment may further include a molybdenum disulfide particle production step of producing the molybdenum disulfide particles.

[0155] Hereinafter, an example of a method for producing molybdenum disulfide particles will be described.

[0156] <Method for producing molybdenum disulfide particles>

[0157] The molybdenum disulfide particles can be produced, for example, by a molybdenum disulfide particle production process comprising heating molybdenum trioxide particles having an average primary particle size of 2 nm to 1000 nm at a temperature of 200 to 1000° C. in the presence of a sulfur source.

[0158] As another embodiment, the molybdenum disulfide particles can be produced, for example, by the following molybdenum disulfide particle production process, which comprises heating the molybdenum trioxide particles obtained by the molybdenum trioxide particle production process described later at a temperature of 200 to 1000° C. in the presence of a sulfur source.

[0159] The average particle size of the primary particles of molybdenum trioxide particles refers to the average primary particle size of 50 randomly selected primary particles obtained by photographing the molybdenum trioxide particles using a scanning electron microscope (SEM) or a transmission electron microscope (TEM), measuring the major axis (the Feret diameter of the longest observed part) and the minor axis (the shorter Feret diameter in a direction perpendicular to the Feret diameter of the longest part) of the smallest unit particle constituting the agglomerate on the two-dimensional image, and taking the average value as the primary particle size.

[0160] In the method for producing the molybdenum disulfide particles, the average particle size of the primary particles of the molybdenum trioxide particles is preferably 1 μm or less. In terms of reactivity with sulfur, it is more preferably 600 nm or less, further preferably 400 nm or less, and particularly preferably 200 nm or less. The average particle size of the primary particles of the molybdenum trioxide particles may be 2 nm or more, 5 nm or more, or 10 nm or more.

[0161] The molybdenum trioxide particles used in the manufacture of the molybdenum disulfide particles are preferably composed of an aggregate of primary particles containing a β crystal structure of molybdenum trioxide. The molybdenum trioxide particles have better reactivity with sulfur than conventional molybdenum trioxide particles whose crystal structure consists only of α crystals, and contain a β crystal structure of molybdenum trioxide, so that the conversion rate R to MoS2 can be increased in the reaction with the sulfur source. C .

[0162] The β crystal structure of molybdenum trioxide can be confirmed by the presence of a peak attributable to the (011) plane of the β crystal of MoO3 (2θ: near 23.01°, No. 86426 (Inorganic Crystal Structure Database (ICSD))) in a pattern obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source. The α crystal structure of molybdenum trioxide can be confirmed by the presence of a peak attributable to the (021) plane of the α crystal of MoO3 (2θ: near 27.32°, No. 166363 (Inorganic Crystal Structure Database (ICSD))).

[0163] Regarding the above-mentioned molybdenum trioxide particles, in the pattern obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source, the ratio of the peak intensity of the (011) plane belonging to the β crystal of MoO3 to the peak intensity of the (021) plane belonging to the α crystal of MoO3 (2θ: around 27.32°_No.166363 (Inorganic Crystal Structure Database (ICSD))) (β(011) / α(021)) is preferably greater than 0.1.

[0164] The peak intensity attributable to the (011) plane of the β crystal of MoO3 and the peak intensity attributable to the (021) plane of the α crystal of MoO3 are read out for each of the maximum intensities of the peaks to determine the ratio (β(011) / α(021)).

[0165] In the molybdenum trioxide particles, the ratio (β(011) / α(021)) is preferably 0.1 to 10.0, more preferably 0.2 to 10.0, and particularly preferably 0.4 to 10.0.

[0166] The β crystal structure of molybdenum trioxide can also be seen in the Raman spectrum obtained by Raman spectroscopy at wave numbers 773 and 848 cm -1 and 905cm -1 The α crystal structure of molybdenum trioxide can be confirmed by the presence of peaks at wave numbers 663 and 816 cm -1 and 991cm -1 The presence of the peak was confirmed.

[0167] The average particle size of primary particles of the molybdenum trioxide particles may be 5 nm or more and 2000 nm or less.

[0168] Examples of the sulfur source include sulfur and hydrogen sulfide, and these may be used alone or in combination of two.

[0169] The method for producing the above-mentioned molybdenum disulfide particles may also include: heating the molybdenum trioxide particles composed of an aggregate of primary particles having a β crystal structure of molybdenum trioxide at a temperature of 100 to 800° C. in the absence of a sulfur source, and then heating at a temperature of 200 to 1000° C. in the presence of a sulfur source.

[0170] The heating time in the presence of a sulfur source may be any time period as long as the sulfurization reaction proceeds sufficiently, and may be 1 to 20 hours, 2 to 15 hours, or 3 to 10 hours.

[0171] In the method for producing the molybdenum disulfide particles, the feed ratio of the amount of S in the sulfur source relative to the amount of MoO3 in the molybdenum trioxide particles is preferably a condition in which the sulfurization reaction is fully carried out. The amount of S in the sulfur source is preferably 450 mol% or more, more preferably 600 mol% or more, and further preferably 700 mol% or more relative to 100 mol% of the amount of MoO3 in the molybdenum trioxide particles. The amount of S in the sulfur source may be 3000 mol% or less, 2000 mol% or less, or 1500 mol% or less relative to 100 mol% of the amount of MoO3 in the molybdenum trioxide particles.

[0172] In the method for producing the molybdenum disulfide particles, the heating temperature in the presence of the sulfur source may be any temperature at which the sulfurization reaction proceeds sufficiently, and is preferably 320° C. or higher, more preferably 340° C. or higher, and further preferably 360° C. or higher. In addition, the heating temperature may be 320 to 1000° C., 340 to 1000° C., or 360 to 500° C. By setting the heating temperature to a low temperature, the crystallinity of the molybdenum disulfide particles decreases, and the abundance ratio of the amorphous phase can be increased.

[0173] In the above-mentioned method for manufacturing molybdenum disulfide particles, as a post-treatment, the obtained molybdenum disulfide particles can be cooled and then heated as needed. In this heat treatment, for example, it is preferred to sinter the molybdenum disulfide particles under an inactive environment. By heating and sintering the obtained molybdenum disulfide particles, the crystallization of the amorphous phase can be promoted and the crystallinity can be improved. In addition, along with the improvement of the crystallinity, a 2H crystal structure and a 3R crystal structure are newly generated, respectively, and the abundance ratio of the 2H crystal structure to the 3R crystal structure changes. When reheating is performed as a post-treatment in this way, the abundance ratio of the 3R crystal structure can be improved. In addition, by changing the temperature when the obtained molybdenum disulfide particles are heated, the abundance ratio of the 2H crystal structure to the 3R crystal structure can be adjusted.

[0174] By heating and sintering the obtained molybdenum disulfide particles at a predetermined temperature or higher, a second crystalline phase composed of crystallites having a crystallite size of 20 nm or less, preferably 10 nm or less, is newly generated when the amorphous phase is transformed into a 2H crystal structure. At this time, in the 2H crystal structure, when crystallites having a crystallite size of 10 nm or less exist before the heating of the molybdenum disulfide particles, the crystallites grow to a crystallite size of 100 nm or more after the heating of the molybdenum disulfide particles, thereby generating a first crystalline phase composed of the grown crystallites.

[0175] From the viewpoint of increasing the abundance ratio of the crystalline phase of the 3R crystal structure and reducing the abundance ratio of the first crystal phase of the 2H crystal structure as much as possible, the heating temperature of the molybdenum disulfide particles in the post-treatment is preferably 500 to 900°C, more preferably 500 to 800°C.

[0176] In addition, the heating rate of the molybdenum disulfide particles in the post-treatment is preferably 1° C. / min or more and 50° C. / min or less, and more preferably 2° C. / min or more and 10° C. / min or less.

[0177] In the method for producing the molybdenum disulfide particles, the molybdenum trioxide particles preferably have a MoO3 content of 99.5% or more as measured by X-ray fluorescence (XRF). This can increase the conversion rate R to MoS2. C , high-purity molybdenum disulfide with good storage stability can be obtained without worrying about the formation of disulfide from impurities.

[0178] The specific surface area of ​​the molybdenum trioxide particles measured by the BET method is preferably 10 m 2 / g~100m 2 / g.

[0179] In the above-mentioned molybdenum trioxide particles, the above-mentioned specific surface area is preferably 10 m 2 / g or more, more preferably 20m 2 / g or more, more preferably 30m 2 In the above molybdenum trioxide particles, the molybdenum trioxide particles preferably have a molar mass of 100 m / g or more in terms of ease of production. 2 / g or less, also 90m 2 / g or less, also 80m 2 / g or less.

[0180] In the radial distribution function of the molybdenum trioxide particles obtained from the extended X-ray absorption fine structure (EXAFS) pattern of the K absorption edge of molybdenum, the intensity I of the peak due to Mo-O and the intensity II of the peak due to Mo-Mo are O The ratio (I O / IIO ) is preferably greater than 1.1.

[0181] For the intensity of the peak due to Mo-O O , and the peak intensity II caused by Mo-Mo O , read the maximum intensity of the peaks respectively, and calculate the above ratio (I O / II O ). It is believed that the above ratio (I O / II O ) is a standard for obtaining the β crystal structure of MoO3 in molybdenum trioxide particles. O / II O ) is larger, the reactivity with sulfur is better.

[0182] In the above-mentioned molybdenum trioxide particles, the above-mentioned ratio (I O / II O ) is preferably 1.1 to 5.0, may be 1.2 to 4.0, or may be 1.2 to 3.0.

[0183] (Method for producing molybdenum trioxide particles)

[0184] The method for producing the composite according to the embodiment may further include a molybdenum trioxide production step of producing the molybdenum trioxide particles.

[0185] The molybdenum trioxide particles can be produced by the following molybdenum trioxide production process, which includes gasifying a molybdenum oxide precursor compound to form molybdenum trioxide vapor, and cooling the molybdenum trioxide vapor.

[0186] The method for manufacturing the above-mentioned molybdenum trioxide particles includes calcining a raw material mixture, wherein the raw material mixture contains a molybdenum oxide precursor compound and a metal compound other than the above-mentioned molybdenum oxide precursor compound, gasifying the above-mentioned molybdenum oxide precursor compound to form molybdenum trioxide vapor, and the proportion of the above-mentioned metal compound is preferably less than 70% by mass in terms of oxide conversion relative to 100% by mass of the above-mentioned raw material mixture.

[0187] The method for producing the molybdenum trioxide particles can be used Figure 1 The manufacturing device 1 shown is appropriately implemented.

[0188] Figure 1 1 is a schematic diagram showing an example of a production apparatus for producing molybdenum trioxide particles, which are a raw material of the molybdenum disulfide particles of the present embodiment.

[0189] like Figure 1As shown, the manufacturing device 1 comprises: a calcining furnace 2, which calcines a molybdenum trioxide precursor compound or the raw material mixture to gasify the molybdenum trioxide precursor compound; a cross (cross) type cooling pipe 3, which is connected to the calcining furnace 2 and atomizes the molybdenum trioxide vapor gasified by the calcining; and a recovery machine 4, which is a recovery mechanism for recovering the molybdenum trioxide particles atomized by the cooling pipe 3. At this time, the calcining furnace 2 and the cooling pipe 3 are connected via an exhaust port 5. In addition, the cooling pipe 3 is respectively provided with an opening adjustment damper 6 at the left end and an external gas intake port (not shown) at the upper end. An observation window 7 is provided. The recovery machine 4 is connected to an exhaust device 8 as a first air supply mechanism. The exhaust device 8 is used to exhaust air, and the internal air of the recovery machine 4 and the cooling pipe 3 is sucked, and the external air is blown to the cooling pipe 3 from the opening adjustment damper 6 of the cooling pipe 3. That is, the exhaust device 8 exerts a suction function, and the cooling pipe 3 is passively supplied with air. Furthermore, the production apparatus 1 may include an external cooling device 9 , whereby the cooling conditions of the molybdenum trioxide vapor generated from the sintering furnace 2 can be arbitrarily controlled.

[0190] By opening the opening adjustment damper 6, air is sucked in from the external air intake port, and the molybdenum trioxide vapor vaporized in the sintering furnace 2 is cooled in the air environment to produce molybdenum trioxide particles, thereby making the above ratio (I O / II O ) is greater than 1.1, it is easy to obtain the β crystal structure of MoO3 in the molybdenum trioxide particles. When liquid nitrogen is used to cool the molybdenum trioxide vapor, cooling the molybdenum trioxide vapor in a nitrogen environment with a low oxygen concentration can easily increase the oxygen defect density and reduce the above ratio (I O / II O ).

[0191] The molybdenum oxide precursor compound is not particularly limited as long as it is a substance that forms molybdenum trioxide vapor by calcining, and examples thereof include metallic molybdenum, molybdenum trioxide, molybdenum dioxide, molybdenum sulfide, ammonium molybdate, phosphomolybdic acid (H3PMo 12 O 40 ), silicomolybdic acid (H4SiMo 12 O 40 ), aluminum molybdate, silicon molybdate, magnesium molybdate (MgMo n O 3n+1 (n = 1 ~ 3)), sodium molybdate (Na2Mo n O 3n+1 (n = 1 to 3)), titanium molybdate, iron molybdate, potassium molybdate (K2Mo n O 3n+1 (n = 1 to 3)), zinc molybdate, boron molybdate, lithium molybdate (Li2Mo n O 3n+1(n=1-3)), cobalt molybdate, nickel molybdate, manganese molybdate, chromium molybdate, cesium molybdate, barium molybdate, strontium molybdate, yttrium molybdate, zirconium molybdate, copper molybdate, etc. These molybdenum oxide precursor compounds can be used alone or in combination of two or more. The form of the molybdenum oxide precursor compound is not particularly limited, for example, it can be a powder such as molybdenum trioxide, or a liquid such as an aqueous solution of ammonium molybdate, but preferably a powder with good handling and energy efficiency.

[0192] As the molybdenum trioxide precursor compound, it is particularly preferred to use commercially available α-crystal molybdenum trioxide. In addition, when ammonium molybdate is used as the molybdenum oxide precursor compound, it is converted into thermodynamically stable molybdenum trioxide by calcination, so the vaporized molybdenum oxide precursor compound becomes the above-mentioned molybdenum trioxide.

[0193] The molybdenum trioxide vapor may also be formed by calcining a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound.

[0194] Among these, the molybdenum oxide precursor compound preferably contains molybdenum trioxide from the viewpoint of easily controlling the purity, average particle size of primary particles, and crystal structure of the obtained molybdenum trioxide powder.

[0195] The molybdenum oxide precursor compound and the metal compound other than the above-mentioned molybdenum oxide precursor compound may generate an intermediate. Even in this case, the intermediate can be decomposed by calcination to vaporize molybdenum trioxide in a thermodynamically stable form.

[0196] As the metal compound other than the above-mentioned molybdenum oxide precursor compound, among these, aluminum compounds are preferably used to prevent damage to the sintering furnace. However, metal compounds other than the above-mentioned molybdenum oxide precursor compound may not be used in order to improve the purity of the molybdenum trioxide particles.

[0197] The metal compound other than the molybdenum oxide precursor compound is not particularly limited, and examples thereof include aluminum compounds, silicon compounds, titanium compounds, magnesium compounds, sodium compounds, potassium compounds, zirconium compounds, yttrium compounds, zinc compounds, copper compounds, iron compounds, etc. Among these, the aluminum compound, silicon compound, titanium compound or magnesium compound is preferably used as the metal compound.

[0198] The molybdenum oxide precursor compound and the metal compound other than the molybdenum oxide precursor compound may generate an intermediate. Even in this case, the intermediate can be decomposed by calcination to vaporize molybdenum trioxide in a thermodynamically stable form.

[0199] As the metal compound other than the molybdenum oxide precursor compound, an aluminum compound is preferably used to prevent damage to the sintering furnace. In the above production method, the metal compound other than the molybdenum oxide precursor compound may not be used to improve the purity of the molybdenum trioxide powder.

[0200] Examples of the aluminum compound include aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, transition alumina (γ-alumina, δ-alumina, θ-alumina, etc.), α-alumina, and mixed alumina having two or more crystal phases.

[0201] The raw material mixture contains a molybdenum oxide precursor compound and a metal compound other than the above-mentioned molybdenum oxide precursor compound. When the raw material mixture is calcined, the content ratio of the above-mentioned molybdenum oxide precursor compound relative to 100 mass % of the above-mentioned raw material mixture is preferably 40 mass % or more and 100 mass % or less, and may also be 45 mass % or more and 100 mass % or less, and may also be 50 mass % or more and 100 mass % or less.

[0202] The calcination temperature varies depending on the molybdenum oxide precursor compound, the metal compound, the desired molybdenum trioxide particles, etc., but is generally preferably set to a temperature at which the intermediate can be decomposed. For example, when a molybdenum compound is used as the molybdenum oxide precursor compound and an aluminum compound is used as the metal compound, aluminum molybdate may be formed as an intermediate, so the calcination temperature is preferably 500 to 1500° C., more preferably 600 to 1550° C., and further preferably 700 to 1600° C.

[0203] The firing time is not particularly limited, and may be, for example, 1 minute to 30 hours, 10 minutes to 25 hours, or 100 minutes to 20 hours.

[0204] The heating rate varies depending on the properties of the molybdenum oxide precursor compound used, the above-mentioned metal compound, and the desired molybdenum trioxide particles, but from the perspective of manufacturing efficiency, it is preferably 0.1°C / minute to 100°C / minute, more preferably 1°C / minute to 50°C / minute, and even more preferably 2°C / minute to 10°C / minute.

[0205] The internal pressure in the calcining furnace is not particularly limited, and may be either positive pressure or reduced pressure, but from the viewpoint of appropriately discharging the molybdenum oxide precursor compound from the calcining furnace to the cooling pipe, calcining is preferably carried out under reduced pressure. As a specific degree of reduced pressure, preferably -5000Pa to -10Pa, more preferably -2000Pa to -20Pa, and further preferably -1000Pa to -50Pa. When the degree of reduced pressure is above -5000Pa, high air tightness and mechanical strength of the calcining furnace will not be excessively required, and the manufacturing cost can be reduced, so it is preferred. On the other hand, when the degree of reduced pressure is below -10Pa, it is possible to prevent the molybdenum oxide precursor compound from clogging at the discharge port of the calcining furnace, so it is preferred.

[0206] Furthermore, when gas is blown into the calcining furnace during the calcining process, the temperature of the blown gas is preferably 5 to 500°C, more preferably 10 to 100°C.

[0207] The gas blowing speed is preferably 1 L / min to 500 L / min, and more preferably 10 L / min to 200 L / min, relative to the effective volume of 100 L of the firing furnace.

[0208] The temperature of the vaporized molybdenum trioxide vapor varies depending on the type of molybdenum oxide precursor compound used, and is preferably 200 to 2000° C., and more preferably 400 to 1500° C. Furthermore, when the temperature of the vaporized molybdenum trioxide vapor is 2000° C. or less, there is generally a tendency that the vaporized molybdenum trioxide vapor can be easily particle-formed by the air supply of external gas (0 to 100° C.) in the cooling pipe.

[0209] The discharge rate of the molybdenum trioxide vapor discharged from the calcining furnace can be controlled by the amount of the molybdenum oxide precursor compound used, the amount of the metal compound, the temperature of the calcining furnace, the blowing of the gas into the calcining furnace, and the diameter of the exhaust port of the calcining furnace. The discharge rate of the molybdenum trioxide vapor from the calcining furnace to the cooling pipe varies depending on the cooling capacity of the cooling pipe, but is preferably 0.001 g / min or more and 100 g / min or less, and more preferably 0.1 g / min or more and 50 g / min or less.

[0210] The content of molybdenum trioxide vapor contained in the gas exhausted from the calcining furnace is preferably 0.01 mg / L or more and 1000 mg / L or less, and more preferably 1 mg / L or more and 500 mg / L or less.

[0211] Next, the molybdenum trioxide vapor is cooled and formed into particles.

[0212] The cooling of the molybdenum trioxide vapor is performed by setting the cooling pipe to a low temperature. At this time, as cooling means, there can be listed: cooling by blowing gas into the cooling pipe as described above, cooling by a cooling mechanism possessed by the cooling pipe, cooling by an external cooling device, etc.

[0213] The cooling of molybdenum trioxide vapor is preferably carried out in an air environment. By cooling molybdenum trioxide vapor in an air environment to make molybdenum trioxide particles, the above ratio (I O / II O ) is greater than 1.1, it is easy to obtain the β crystal structure of MoO3 in the molybdenum trioxide particles.

[0214] The cooling temperature (temperature of the cooling pipe) is not particularly limited, but is preferably -100 to 600°C, more preferably -50 to 400°C.

[0215] The cooling rate of the molybdenum trioxide vapor is not particularly limited, but is preferably 100°C / s or more and 100,000°C / s or less, and more preferably 1,000°C / s or more and 50,000°C / s or less. Furthermore, the faster the cooling rate of the molybdenum trioxide vapor, the more likely it is that molybdenum trioxide particles with a smaller particle size and a larger specific surface area can be obtained.

[0216] When the cooling means is cooling by blowing gas into the cooling pipe, the temperature of the blown gas is preferably -100 to 300°C, more preferably -50 to 100°C.

[0217] In addition, the gas blowing speed is preferably 0.1 m 3 / min or more and 20m 3 / min or less, more preferably 1m 3 / min or more and 10m 3 / min or less. When the air supply speed is 0.1m 3 / min or more, a higher cooling rate can be achieved, which can prevent clogging of the cooling pipe, so it is preferred. On the other hand, when the gas supply speed is 20m 3 / min or less, there is no need for an expensive first air supply mechanism (exhaust fan, etc.), which can reduce the manufacturing cost and is therefore preferred.

[0218] The particles obtained by cooling the molybdenum trioxide vapor are transported to a recovery machine and recovered.

[0219] In the method for producing the molybdenum trioxide particles, the particles obtained by cooling the molybdenum trioxide vapor may be calcined again at a temperature of 100 to 320°C.

[0220] That is, the molybdenum trioxide particles obtained by the above-mentioned method for manufacturing molybdenum trioxide particles can also be calcined again at a temperature of 100 to 320°C. The calcination temperature for the re-calcination can be 120 to 280°C, or 140 to 240°C. The calcination time for the re-calcination can be, for example, 1 minute to 4 hours, 10 minutes to 5 hours, or 100 minutes to 6 hours. However, by calcining again, part of the β crystal structure of molybdenum trioxide will disappear. If calcined at a temperature above 350°C for 4 hours, the β crystal structure in the molybdenum trioxide particles disappears, the above ratio (β(011) / α(021)) becomes 0, and the reactivity with sulfur is impaired.

[0221] By the method for producing molybdenum trioxide particles described above, molybdenum trioxide particles suitable for producing the above-mentioned molybdenum disulfide particles can be produced.

[0222] <<Hydrogen Production Catalyst>>

[0223] The composite of the embodiment can be suitably used as a catalyst in the hydrogen evolution reaction (HER) (sometimes referred to as a "hydrogen production catalyst" in this specification). In addition, the composite of the embodiment can also be used as a hydrogen production catalyst by being used in combination with a conductive material. That is, as a preferred hydrogen production catalyst, for example, a hydrogen production catalyst containing the composite of the embodiment can be cited, and the above-mentioned hydrogen production catalyst can also contain a conductive material in addition to the composite of the embodiment. The catalytic activity of the hydrogen production catalyst containing the composite of the embodiment and the conductive material in the hydrogen evolution reaction (HER) becomes higher.

[0224] The conductive material mentioned above may be a known conductive material.

[0225] Examples of the conductive material include carbon and metals having high conductivity.

[0226] The hydrogen production catalyst may contain only one type of the conductive material or two or more types of the conductive material.

[0227] Examples of the conductive material include carbon black such as acetylene black, Cabot black, and ketjen black, graphite, carbon fiber, metal powder, etc. Ketjen black has a high specific surface area and conductivity, and is also excellent in suppressing the aggregation of molybdenum sulfide.

[0228] Examples of the metal as the conductive material include gold, silver, copper, aluminum, rhodium, molybdenum, tungsten, iron, nickel, cobalt, and indium.

[0229] The metal as the conductive material is different from the palladium of the composite of the embodiment, and is simply mixed with the composite of the embodiment in the hydrogen production catalyst.

[0230] The metals contained in the hydrogen production catalyst as the conductive material may be only one kind or two or more kinds.

[0231] The hydrogen production catalyst may contain carbon instead of metal as the conductive material, may contain metal instead of carbon, or may contain both metal and carbon.

[0232] In the hydrogen production catalyst, the content of the conductive material is preferably 0.1 to 100 parts by mass, and more preferably 0.5 to 50 parts by mass, based on 100 parts by mass of the composite of the embodiment.

[0233] In the hydrogen production catalyst, relative to the total mass (100 mass %) of the hydrogen production catalyst, the ratio of the total content of the composite of the embodiment and the above-mentioned conductive material is preferably 80 mass % or more, more preferably 90 mass % or more, and further preferably 95 mass % or more, for example, it can be any one of 97 mass % or more and 99 mass % or more, or it can be 100 mass %. By making the above ratio above the above lower limit, the catalytic activity of the hydrogen production catalyst in the hydrogen evolution reaction (HER) becomes higher. The above ratio can be as long as it is less than 100 mass %.

[0234] <<Catalyst ink>>

[0235] The above-mentioned hydrogen production catalyst is suitably used as a component contained in the catalyst ink.

[0236] The catalyst ink of the embodiment contains the composite of the embodiment and a solvent.

[0237] The catalyst ink of the embodiment can contain the composite of the embodiment, a polymer electrolyte, and a solvent.

[0238] The catalyst ink of the present embodiment may further contain a conductive material. Examples of the type and content of the conductive material include the types and contents of the conductive materials exemplified above.

[0239] The catalyst ink can be applied to, for example, a working electrode substrate to form a catalyst layer.

[0240] As the polymer electrolyte, a polymer electrolyte generally used in the formation of the catalyst layer can be used. Specifically, examples include: a perfluorocarbon polymer having a sulfonic acid group (e.g., Nafion (registered trademark)), a hydrocarbon polymer compound having a sulfonic acid group, a polymer compound doped with an inorganic acid such as phosphoric acid, an organic / inorganic hybrid polymer partially substituted with a proton conductive functional group, and a proton conductor obtained by impregnating a polymer matrix with a phosphoric acid solution or a sulfuric acid solution.

[0241] As the solvent, there can be cited a solvent that can disperse the composite of the embodiment and can be applied to a working electrode substrate to form a catalyst layer. As the above-mentioned solvent, preferably, it contains alcohols such as 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 1-hexanol, 2-hexanol, 1-heptanol, and 2-heptanol.

[0242] Example

[0243] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the following Examples.

[0244] [Synthesis Example 1] (Reference Example)

[0245] (Manufacturing of molybdenum trioxide particles)

[0246] A sintering furnace equivalent to a heat-resistant container, a cooling pipe provided with an external gas supply port, and a dust collector for recovering molybdenum oxide were prepared. The molybdenum oxide was produced using an RHK simulator (manufactured by Noritake Company Limited) as the sintering furnace and a VF-5N dust collector (manufactured by AMANO Co., Ltd.) as the dust collector.

[0247] 1.5 kg of aluminum hydroxide (manufactured by Nippon Light Metal Co., Ltd.) and 1 kg of molybdenum trioxide (manufactured by Nippon Inorganic Co., Ltd.) were mixed and then added to the sagger, connected to the sintering furnace, cooling pipe and dust collector, and sintered at a temperature of 1100°C for 10 hours. During the sintering process, external air was introduced from the side and lower surface of the sintering furnace (air supply speed: 150 L / min, external air temperature: 25°C). Since molybdenum trioxide evaporates in the furnace, it is cooled near the dust collector and precipitated into particles, so the molybdenum trioxide is recovered by the dust collector.

[0248] After the firing, 1.0 kg of blue powdered aluminum oxide and 0.8 kg of molybdenum trioxide were collected by a dust collector and taken out from the sagger.

[0249] The primary particle size of the recovered molybdenum trioxide was 1 μm or less, and the purity of the molybdenum trioxide was confirmed to be 99.8% by fluorescent X-ray measurement.

[0250] (Manufacturing of Molybdenum Disulfide Particles)

[0251] Add 40.0 g (277.9 mmol) of the molybdenum trioxide produced above and 40.0 g (1250 mmol, 4.5 equivalents relative to Mo atoms) of sulfur powder (manufactured by Kanto Chemical Co., Ltd.) to an alumina crucible, and use a stirring rod to mix to make the powder uniform. After mixing, cover the alumina crucible and put it into a high-temperature environment sintering furnace (manufactured by MOTOYAMA, SKM-2030P-OP). After evacuating the inside of the furnace, replace it with nitrogen and then sinter. The sintering conditions are to increase the temperature at a rate of 5°C / min from room temperature of 25°C, and maintain it at 500°C for 4 hours. During the sintering process, nitrogen is blown at 0.5 L / min. Thereafter, the furnace is cooled by natural cooling to obtain 44.5 g of molybdenum disulfide particles.

[0252] (Manufacturing of composites)

[0253] [Example 1]

[0254] 100 mg of the molybdenum disulfide particles obtained in the above-mentioned Synthesis Example 1 were mixed with 25 mL of methanol (Kanto Chemical Co., Ltd. reagent, CH 3 OH), and ultrasonically treated for 30 minutes to obtain a dispersion in which the molybdenum disulfide particles were dispersed in methanol.

[0255] Palladium acetate (Kanto Chemical Co., Ltd. reagent, Pd(CH3COO)2) 4.3 mg was mixed with methanol 25 mL, and the palladium acetate was dissolved in methanol, and the resulting solution was added to the above-mentioned dispersion in a stirred state. Then, under light irradiation (generally in a bright indoor environment), it was stirred at room temperature for more than 2 hours to obtain a precipitate. The precipitate was recovered by a centrifuge, ultrasonically cleaned in water 3 times, and then vacuum dried to obtain the composite particles of Example 1.

[0256] [Examples 2 to 4]

[0257] In Example 1, the amounts of palladium acetate and methanol used (methanol is used for the dispersion of molybdenum disulfide particles and the palladium solution, respectively, in an amount half of the values ​​recorded in the table) were changed as described in Table 1. Otherwise, the composite particles of Examples 2 to 4 were obtained in the same manner as in Example 1 above.

[0258] [Comparative Example 1]

[0259] In Example 2, commercially available carbon black (KB) (manufactured by Lion Specialty Chemicals Co., Ltd., Ketjen Black, product number: EC300J, median particle size D 50The particles of Comparative Example 1 were obtained in the same manner as in Example 2, except that 100 mg of molybdenum disulfide particles (>40 nm) were used instead of 100 mg of molybdenum disulfide particles obtained in Synthesis Example 1.

[0260] [Comparative Example 2]

[0261] As the particles of Comparative Example 2, commercially available molybdenum disulfide particles (manufactured by Kanto Chemical Co., Ltd.) were used.

[0262] The particles of Synthesis Example 1, Examples 1 to 4, and Comparative Examples 1 and 2 were used as samples and the following evaluations were performed.

[0263] <<Evaluation>>

[0264] [XRF analysis]

[0265] Using a fluorescent X-ray analyzer Primus IV (manufactured by Rigaku), about 20 to 30 mg of the sample was placed on filter paper and covered with a PP film for composition analysis. The amount of palladium, molybdenum, and sulfur obtained from the XRF analysis results were obtained as the palladium content (mass %), molybdenum content (mass %), and sulfur content (mass %) relative to 100% by mass of the sample particles.

[0266] [XRD crystal structure determination]

[0267] The sample holder filled with the sample to a depth of 0.5 mm was mounted on a wide-angle X-ray diffraction (XRD) apparatus (Ultima IV manufactured by Rigaku Corporation) and measured under the conditions of Cu / Kα radiation, 40 kV / 40 mA, scanning speed 2θ=2° / min, and scanning range 2θ=10° or more and 70° or less.

[0268] [Determination of crystallite size]

[0269] SmartLab 9kV (manufactured by Rigaku Co., Ltd.) was used as an X-ray diffraction device, a scintillation counter detector was used as a detector, and PDXL2 was used as the analysis software for measurement. The measurement method was the 2θ / θ method, and the average crystallite size was calculated using the Scherrer formula based on the half-height width of the peak appearing at 2θ=14.4°±0.5°. Furthermore, as measurement conditions, the scanning speed (2θ) was 2.0° / min, the scanning range (2θ) was 10-70°, the spacing (2θ) was 0.02°, and the device standard width was set to none.

[0270] [XPS analysis]

[0271] The prepared sample was fixed on a carbon tape using an X-ray photoelectron spectroscopy (XPS) apparatus (manufactured by Thermo Fisher Scientific, Japan, K-Alpha), and composition analysis was performed under the following conditions.

[0272] X-ray source: monochromatic AlKα ray, 12kV, 6mA

[0273] ·Measurement diameter: 400μm

[0274] ·Electrical correction: No

[0275] X-ray take-off angle: 90°

[0276] [Measurement of BET specific surface area]

[0277] The specific surface area was measured using a specific surface area meter (BELSORP-mini, manufactured by Microtrac BEL Co., Ltd.), and the surface area per 1 g of the sample measured by the BET method was calculated from the nitrogen adsorption amount, and this was taken as the specific surface area.

[0278] [Median particle size D 50 Determination of

[0279] 0.1 g of the sample powder was added to 20 cc of acetone, and ultrasonic treatment was performed in an ice bath for 4 hours. Then, the concentration was appropriately adjusted to the measurable range of a dynamic light scattering particle size distribution measuring device (manufactured by Microtrac BEL, Nanotrac Wave II) using acetone to obtain a measurement sample. Using the measurement sample, the particle size distribution in the range of 0.0001 μm to 10 μm was measured using a dynamic light scattering particle size distribution measuring device, and the particle size when the volume cumulative % ratio became 50%, that is, the median particle size D was calculated. 50 Furthermore, for the median particle size D 50 For particles larger than 10 μm (Comparative Example 2), the solution was adjusted in the same manner, and the particle size distribution in the range of 0.015 μm to 500 μm was measured by a laser diffraction particle size distribution measuring device (manufactured by Shimadzu Corporation, SALD-7000), and the median particle size D was calculated. 50 .

[0280] [Measurement of Average Particle Size of Palladium Particles]

[0281] For palladium particles confirmed on a two-dimensional image obtained by photographing the sample powder using a high-resolution transmission electron microscope (HR-TEM, manufactured by JEOL Ltd., JEM-ARM300F), the maximum length of the distance between two points on the contour line of 50 randomly selected palladium particles (wherein, palladium particles in a state where multiple palladium particles are aggregated are not selected) is measured, and the average value of the maximum lengths is taken as the average particle size of the palladium particles.

[0282] Table 1 shows the results of the above measurements.

[0283] [Table 1]

[0284]

[0285] The particles of Synthesis Example 1, Examples 1 to 4, and Comparative Examples 1 to 2 have the palladium content, molybdenum content, sulfur content, MoS2 content, MoS2 average crystallite size, average particle size of palladium particles, BET specific surface area, and D 50 .

[0286] The results of XRD analysis are shown in Figure 2 The XRD patterns of the composite particles of Examples 1 to 4 are substantially consistent with the XRD pattern of the molybdenum disulfide particles of Synthesis Example 1. On the other hand, the XRD pattern of the particles obtained using carbon black in Comparative Example 1 is substantially consistent with the XRD pattern of palladium (Pd) of the sample.

[0287] exist Figure 3 Observation images of each particle of Synthesis Example 1, Examples 1 to 4, and Comparative Example 1 obtained by using a transmission electron microscope (TEM, manufactured by JEOL Ltd., JEM-1400) are shown in FIG.

[0288] In the TEM observation images shown here, Examples 3 and 4 and Comparative Example 1 clearly show that spherical particles with a diameter of about 1 to 10 nm are attached or bonded to the molybdenum disulfide particles or the carbon black particles.

[0289] exist Figure 4 2 shows an observation image of the composite particles of Example 2 using a high-resolution transmission electron microscope (HR-TEM, manufactured by JEOL Ltd., JEM-ARM300F) and the results of elemental mapping using energy dispersive X-ray spectroscopy (EDS).

[0290] The element mapping results showed that the Pd density was high at the position corresponding to the spherical particles, which confirmed that the spherical particles with a diameter of about 1 to 10 nm observed by the TEM corresponded to palladium particles containing Pd.

[0291] Regarding the composite particles of Examples 1 to 4, no diffraction pattern derived from the crystal structure of palladium metal was confirmed in the above-mentioned XRD analysis.

[0292] This indicates that Pd in ​​the composite particles of Examples 1 to 4 does not have a crystal structure of palladium metal crystals.

[0293] In addition, the angle values ​​of the peak (peak top) appearing at 2θ=14.4±0.5° in the above XRD analysis are, respectively, Synthesis Example 1: 14.20°, Example 1: 14.20°, Example 2: 14.20°, Example 3: 14.20°, Example 4: 14.20°. Respectively, relative to the MoS2 of Synthesis Example 1, no clear peak shift caused by the addition of Pd was confirmed.

[0294] From this, it is estimated that the crystal structure of the molybdenum disulfide particles of the composite does not undergo a significant change from the crystal structure of the molybdenum disulfide particles of Synthesis Example 1 as a raw material.

[0295] In addition, in the state where metal ions are distributed between layers of a material, etc. as shown in Patent Document 1, the interlayer spacing of MoS2 usually changes. However, in the composite particles of Examples 1 to 4, as described above, no peak shift of 2θ=14.4±0.5° was found. Therefore, it can be confirmed that, unlike the state shown in Patent Document 1, the interlayer spacing of MoS2 has not changed.

[0296] In addition, according to the results of surface analysis of the composite particles of Examples 1 to 4 by X-ray photoelectron spectroscopy (XPS), the values ​​of the peak positions of the Pd 3d spectrum (values ​​of binding energy) are: 5 / 2 :335.5eV、Pd 3d 3 / 2 : 340.8 eV. The valence of Pd read from these binding energy values ​​is 0.

[0297] The above results suggest that the palladium contained in the composite particles of Examples 1 to 4 is different from the state shown in Patent Document 1, and the palladium ions are not distributed between the layers of molybdenum disulfide.

[0298] exist Figure 5 ] A HAADF-STEM image (transmission electron image, manufactured by JEOL Ltd., JEM-ARM300F) and a SEI image (secondary electron image, manufactured by JEOL Ltd., JEM-ARM300F) of the composite particles of Example 2 are shown. Figure 5 The arrow in shows an example of the same palladium particle observed in the HAADF-STEM image and the SEI image.

[0299] In the transmission electron image, information about the sample surface (including the back side of the imaged particles) and the inside of the sample can be obtained, and in the secondary electron image, information about the outermost surface of the sample (excluding the inside and back side of the imaged particles) can be obtained.

[0300] According to the comparison between the transmission electron image and the secondary electron image, since a large number of palladium particle images were also observed in the secondary electron image, it was found that most of the palladium particles existed on the surface of the molybdenum disulfide particles.

[0301] Based on the above, the following findings were obtained: Pd in ​​the composite particles of Examples 1 to 4 does not have a crystal structure of palladium metal crystals, and exists on the surface of molybdenum disulfide particles as palladium particles in the state of an aggregate of zero-valent palladium atoms having no crystal structure.

[0302] Assuming that in MoS2, when Pd is doped to replace Mo to form a crystal structure, or when it exists as ions between layers, most of the Pd atoms contained in the particles exist inside MoS2.

[0303] On the other hand, regarding the composite particles of each example, it is considered that most of the Pd atoms contained in the composite particles constitute palladium particles and exist on the surface of the composite particles.

[0304] (Manufacture of catalyst ink)

[0305] Inks were prepared using the particles of Synthesis Example 1, Examples 1 to 4, and Comparative Examples 1 to 2 as raw materials, and the catalyst performance in the hydrogen evolution reaction (HER) was evaluated by the following method.

[0306] 4 mg of the above-obtained particles (any of the particles of Synthesis Example 1, Examples 1 to 4, and Comparative Examples 1 to 2), carbon black (Ketjen Black, product number: EC300J, median particle size D 0.0407, manufactured by Lion Specialty Chemicals Co., Ltd.) and 1.5 mg of carbon black were added. 50 : 40nm) 2mg, 5% Nafion dispersion (Fujifilm Wako Pure Chemical Industries, Ltd., Nafion dispersion solution) 40μL, and 1mL of ethanol were mixed and ultrasonicated for 1 hour to disperse the particles, thereby preparing ink (dispersion liquid). 20μL of the obtained ink was applied to the electrode surface. After the surface liquid dried naturally, it was moved to a vacuum dryer and dried at 60°C for more than 6 hours to obtain a test electrode. The hydrogen evolution reaction (HER) activity of the obtained test electrode was evaluated by a three-electrode method. The evaluation conditions were performed by the LSV method with a scanning voltage range of -0.3V to 0V and a scanning speed of 5mV / S.

[0307] Table 1 shows the evaluation results of the above catalyst performance.

[0308] The inks containing the composite particles of Examples 1 to 4 had a current density of 10 mA cm-1 compared to the inks containing the particles of Synthesis Example 1 or Comparative Examples 1 to 2. -2 The overvoltage value at 0.1 V was low (comparative example 2 could not be measured), and the current density value at -0.3 V was high.

[0309] The above results show that the composites of Examples 1 to 4, which are formed by combining molybdenum disulfide particles and palladium particles, can exhibit excellent catalytic activity.

[0310] Each configuration and combination thereof in each embodiment is an example, and addition, omission, substitution, and other changes of the configuration may be made without departing from the gist of the present invention. In addition, the present invention is not limited to each embodiment, but only to the scope of claims.

[0311] Explanation of symbols

[0312] 1: Manufacturing device

[0313] 2: Firing furnace

[0314] 3: Cooling piping

[0315] 4: Recycling Machine

[0316] 5: Exhaust port

[0317] 6: Opening adjustment damper

[0318] 7: Observation window

[0319] 8: Exhaust device

[0320] 9: External cooling device

Claims

1. A composite comprising molybdenum disulfide particles and palladium particles, wherein the average crystallite size of molybdenum disulfide contained in the molybdenum disulfide particles is 150 nm or less, and the average crystallite size is obtained based on a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement.

2. The composite according to claim 1, wherein The average particle size of the palladium particles is 20 nm or less.

3. The composite according to claim 1 or 2, wherein: The palladium particles exist on the surfaces of the molybdenum disulfide particles.

4. The composite according to claim 1 or 2, wherein: The palladium particles include an aggregate of palladium atoms having no crystal structure.

5. The composite according to claim 1 or 2, wherein The median particle size D of the composite obtained by dynamic light scattering 50 Below 1000nm.

6. The composite according to claim 1 or 2, wherein: The specific surface area of ​​the composite measured by the BET method is 10 m 2 / g or more and 200m 2 / g or less.

7. The composite according to claim 1 or 2, wherein: The ratio of the palladium content determined by XRF analysis to the total mass of the composite is 0.1 mass % or more.

8. The composite according to claim 1 or 2, wherein: The molybdenum disulfide contained in the molybdenum disulfide particles has a 3R crystal structure.

9. The composite according to claim 1 or 2, wherein: The primary particles of the molybdenum disulfide particles are in the shape of ropes, belts or sheets, and have an average thickness of 50 nm or less. 10 . A catalyst ink comprising the composite according to claim 1 or 2 and a solvent.

11. A method for producing a composite according to claim 1 or 2, comprising the step of mixing molybdenum disulfide particles with a palladium solution, wherein the average crystallite size of molybdenum disulfide contained in the molybdenum disulfide particles is less than 150 nm, and the average crystallite size is obtained based on the peak of 2θ=14.4°±0.5° obtained by X-ray diffraction measurement.

Citation Information

Patent Citations

  • Electric centrifugal compressor

    JP2022123199A